PENGEMBANGAN MEDIA PEMBELAJARAN MENGGUNAKAN MOBILE APLIKASI BERBASIS AUGMENTED REALITY MATERI DIMENSI TIGA KELAS XII SMA NEGERI 4 PEKALONGAN - Syita Fatih 'Adna; Mitia Fatma Ningsih; Amalia Fitri (Jurnal Karya Pendidikan Matematika, 2020)
The purposes of the research were to develop and produce an augmented reality based learning media product of used proper. This research was conducted to 30 third grade students of Social Science Major at Senior High School 4 of Pekalongan. This research used Research and Development (R&D) method with ADDIE model. The conducted steps were analysis, design, development, implementation and evaluation. The data collection instruments used within this research were observation, interview and questionnaire. There were 3 questionnaires: 1) Student’s need questionnaire; 2) Validity questionnaire; and 3) Practicality questionnaire. The data analyses used were learning media validity analysis and students’ response practicality analysis. Based on the result of the research, the average total aspect from all validators reached 4,10. It showed that the developed learning media could be categorized as valid. Meanwhile from the students’ response questionnaire showed that the practicality value reached 92%. It indicated that the learning media used was very practical. Therefore, it can be concluded that the learning media is feasible as it is valid and very practical. The learning media can be utilized as a learning source for students in three dimension materials.Keywords: Learning Media, Mobile Application, Augmented Reality